Influenza A(H5N1) Virus Clade 2.3.2.1a in Traveler Returning to Australia from India, 2024 - Yi-Mo Deng; Michelle Wille; Clyde Dapat; Ruopeng Xie; Olivia Lay; Heidi Peck; Andrew J. Daley; Vijaykrishna Dhanasakeran; Ian G. Barr (Emerging Infectious Diseases)
We report highly pathogenic avian influenza A(H5N1) virus clade 2.3.2.1a in a child traveler returning to Australia from India. The virus was a previously unreported reassortant consisting of clade 2.3.2.1a, 2.3.4.4b, and wild bird low pathogenicity avian influenza gene segments. These findings highlight surveillance gaps in South Asia.